Enkripsi Aturan Dinamis pada Aplikasi Pembayaran Gerak - Emir Husni; Danang Triantoro Murdiansyah (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2016)
The trend of financial transactions using mobile phone or mobile payment is increasing. Using the mobile payment service, user can save money on the mobile phone and separate the money from prepaid bills. In order to protect the user, provider must equip the mobile payment service with transaction security, such as secure mobile payment application. This paper offers a safety feature which is used for mobile payment application based on Android operating system. A new method, Dynamic Rule Encryption (DRE), is created. In DRE, the encryption is ruled dynamically. By encrypting data with dynamic rules, DRE can protect the data. DRE also has a function as a token for authentication. DRE Token is generated using dynamic time-based rules. The time reference used in DRE is based on the order of the day in the year (day of the year). Performance measurement in this research is based on the Hamming distance. The test results show that the system performs quite good. The average distance among outputs is about 258 bits of 512 bits input. The results also show that the DRE program’s execution time is quite fast, i.e. not more than 24 ms.